ANALISIS GAYA KEPEMIMPINAN PELAKSANA TUGAS DALAM MENINGKATKAN MOTIVASI KERJA PETUGAS DI LEMBAGA PEMASYARAKATAN KELAS IIB BLITAR - Alfin Hernanda Syahputra; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
This study was conducted to examine, firstly, whether the task executive's leadership style has a significant effect on the performance of correctional officers. Second, whether the influence of leadership style on performance is based on the motivation of the leader. In connection with this problem, the following hypothesis is proposed, Leadership style has a significant influence on the performance of correctional officers. Second, the motivation of correctional officers is based on the influence of leadership style on correctional performance. The purpose of the study was to determine yes or not there was an influence of the executive's leadership style in leading and motivating correctional officers. This research is aimed at the performance problems of correctional officers who have not met expectations. This study uses a descriptive-qualitative method, and obtains data through interviews, results from previous studies, and observations.